ISOLATION AND CHARACTERIZATION OF OLEANOLIC ACID FROM ROOTS OF LANTANA CAMARA - VYAS, NARENDRA; ARGAL, AMEETA (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: The aim of the present study is to isolate oleanolic acid from the roots Lantana camara roots and its chemical characterization by TLC, HPLC and Infra-red spectroscopy methods. Methods: The chemical characterization of isolated compound was done by Thin Layer Chromatography (TLC), High Performance Liquid chromatography (HPLC) and Infrared spectroscopy. Results: The results of spectrophotometric analysis showed that the oleanolic acid isolated from Lantana camara roots gives similar spectral results as shown by standard oleanolic acid. Conclusion: on the basis obtained results of TLC, HPLC and IR spectra and its interpretation, it can be concluded that oleanolic acid isolated from roots of Lantana camara give identical, characteristic signals and absorbance similar to earlier reported reference standards. Â Key Words: Oleanolic acid, Lantana camara, HPLC, FTIR, TLC